Food security effects of smallholders’ participation in apple and mango value chains in north-western Ethiopia - Mengistie Mossie; Alemseged Gerezgiher; Zemen Ayalew; Asres Elias (Agriculture & Food Security, 2021)
Abstract Background While it has identified that linking smallholders in the agri-food value chain remains to be a promising strategy to get out of the poverty trap in many developing countries, less is known about the food security implications of smallholders’ participation in the fruits value chain. This paper examines the effects of apple and mango smallholder farmers’ participation along the value chain, focusing on their household food security in north-western Ethiopia. Methods Primary data for the study were obtained from a random sample of 384 households, 211 of which are fruit value chain participants, and the remainder are non-participants. The study used the propensity score matching (PSM) method to establish a causal relationship between the participation of the fruit value chain and changes in household food security. Results and conclusions Results indicate that participation in the apple and mango value chain has a robust and positive effect on the food security of smallholders as measured by household food consumption in kilocalorie. The unconfoundedness and overlapping assumptions were fulfilled by applying the nearest neighbor and kernel-based matching algorithms. The study confirms that the more apple and mango farmers join the value chain, the higher their household food intake becomes. Support for fruit farmers is, therefore, a promising policy approach that can help improve household food security in rural Ethiopia.